GOTHIC STORY IN THE UKRAINIAN LITERARY PROCESS "AT THE TURN OF THE CENTURY" (BASED ON THE CREATIVE WORKS BY ANDRII CHAIKOVSKYI "COSSACK REVENGE" AND HRYHORII MACHTET "THE CURSED COSSACK") - Stetska, I. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Purpose. The article is devoted to a detailed analysis of Andriy Tchaikovsky’s "Cossack Revenge" and Hryhoriy Machtet’s "Sworn Cossack" through the prism of Gothic poetics. The author singles out and systematizes a set of elements of the Gothic paradigm in the respective texts of the writers; establishes that in the coordinate system of the national variant of literary Gothic, in addition to the presence of demonological characters, the mythologized image of the Cossack-character plays an important role in the stories; traces the transformation of individual artistic details of the pan-European invariant of Gothic poetics on Ukrainian soil. The purpose of the article is to highlight the peculiarities of gothic poetics and its transformation in the novels by Andriy Tchaikovsky "Cossack Revenge" and Hryhoriy Machtet "The Sworn Cossack". Research methodology. The article applies a number of methods that make it possible to highlight the problems raised, in particular, the use of the typological method made it possible to systematize the relevant features ofgothic poetics in the analyzed works; psychoanalytic – to study the functional load of oniric motifs of literary gothic and to explicate the thanatological elements of the figurative and plot level in the gothic story; mythopoetic – to single out and characterize the role of the mythological image in the gothic coordinate system; structuralist – to consider the gothic genre system as an integral structure, where each element determines the specifics of this structure; intertextual – to trace the use of numerous allusions to the relevant folklore motifs. Results. The article investigates the transformation of certain features of the gothic poetics of the world invariant of literary gothic on the material of the works of Andriy Tchaikovsky "Cossack revenge" and Hryhoriy Machtet "Sworn Cossack", and also reveals a number of features inherent in the national variant of the gothic genre, including, in particular, implicit naturalism, mythology, contamination of phantasmagoria and onyric, reduction of the category of horror, ironic worldview. Scientific novelty. The article is the first comprehensive analysis of Andriy Tchaikovsky’s novels "Cossack revenge" and Hryhoriy Machtet’s "The sworn Cossack" through the prism of gothic poetics, as well as a schematic generalization of the attributes of gothic poetics and their modifications in Ukrainian literature in comparison with the world literature. Practical significance. The article can be used in the process of studying literary Gothic as a genre variety, the study of the evolution of its poetics in different periods, as well as for a comprehensive analysis of Gothic as an artistic phenomenon. Scientific results of the research can be used by students in writing term papers and qualification works.